EN TORNO AL RETABLO MAYOR DE LA CATEDRAL DE OVIEDO - Barroso Villar, Julia (Imafronte, 1989)
This retable of first half of the XVI th century, already classified by Professor Gómez Moreno and other scholars as belonging to the Spanish-Flemish styk, may be compared, because of its quality, to the two other great coeval cathedral retables in Toledo and Seville. The former retable keeps a certain parallelism with these latter two, though that in Oviedo has not as great space ambition as the Sevillian one; it is closer to the rerable in Toledo because of its soberer plan, documented as by Giralre of Brussels. Beside Giralte, the collaboration of Juan de Balmaseda and the gluing and gilding completion by León Picardo are also documented. It is quite strange the non contribution of Alonso Berruguere, in spite of his contribution to ihe work was required. To sum up, we outline a reflection upon the hypotheses enounced up to date, referring to iconography, strucrure and style of the work as a whole and to its relation wirh the two other great retables and with the two above mentioned great Spanish-Flemish cathedral retables. As far as regards to rhe relation with the sorrounding space in the main chapel, the whole happens to be like a big tapesrry largely hiding the architectural frame in which ir is inserted.